Epidemiology and seasonal dynamics of internal parasite infections in small ruminants at Ukulinga Research Farm, South Africa - Ahmed, Mawahib Alhag Ali (Journal of Veterinary Medicine and Animal Production, 2021)
An epidemiological study of internal parasite infections of ewes and does was carried out at the University of KwaZulu-Natal, Ukulinga Research Farm in South Africa for 1 year. The experimental animals consisted of a total of 16 animals, including 8 Merino sheep ewes and 8 Ngunigoats does. These animals grazed on kikuyu pasture together with a larger university flock. Parasitological data of nematode egg counts (EPG), infective larvae (L3) from faecal culture and infective larvae found in the pastures were recorded monthly. Coccidian oocysts and live weight were also recorded. The measured parameters showed distinct seasonal effects. The highest level of infections occurred in December and the lowest level of infections occurred in July. In the faeces of the experimental animals Trichostrongylus species were the most prevalent parasites, followed by Strongyloides species, Haemonchus contortus, Nematodirus species, Cooperia species, and on Eimeria species. Seasonal effect was significant (P<0.05) on EPG, the infective larvae of the faecal cultures, pasture L3 stages and Eimeria oocysts counts. Similarities were observed in EPG and live weight gain during the year. Information obtained gave base data for suggesting a control program with a minimum anthelmintic use.